Structural characterisation and immunomodulatory activity of a polysaccharide isolated from lotus (Nelumbo nucifera Gaertn.) root residues. (September 2019) - Hu, Weicheng; Jiang, Yunyao; Xue, Qi; Sun, Fengting; Zhang, Jianmei; Zhou, Jing; Niu, Zhiqiang; Li, Qiuting; Li, Fu; Shen, Ting
Graphical abstract: Highlights: An active lotus root polysaccharide (LRP) was extracted, purified and characterized. LRP has immunomodulatory effects on RAW 264.7 cells. LRP induced macrophage activation via PI3K/Akt and MAPKs signal pathways. LRP could be developed as a potential immunoregulatory agent in functional foods. Abstract: An active water-soluble lotus root polysaccharide (LRP) with average molecular weight of 1.24 × 10 4 Da was purified from lotus ( Nelumbo nucifera Gaertn.) root residues. The structure of LRP was determined to be α-D-(1 → 4)-linked glucopyranosyl moieties with non-reducing terminal α-D-Glc p at O-6 as branches approximately every six residues. An immunological activity assay indicated that LRP significantly promoted the production of nitric oxide, interleukin-6, and tumour necrosis factor-α (TNF-α). LRP induced nuclear translocation of activator protein-1 and nuclear factor-κB. Intriguingly, LRP remarkably increased phosphorylation of upstream signalling molecules, including extracellular signal-regulated kinase, c-Jun N-terminal protein kinase, IκBα, Akt, and p85. Moreover, LRP promoted the secretion of TNF-α and interleukin-2 in cyclophosphamide-induced immunosuppressive mice. Collectively, these results suggest that LRP can improve immunity by enhancing immune function both in vitro and in vivo and this substance might be explored as an immunomodulatory agent for use in dietary supplements.